2014
DOI: 10.4317/jced.51292
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic periodontitis with white blood cell and platelet count - A Case Control Study

Abstract: Objectives:The objective of the study was to determine whether plasma levels of white blood corpuscles (WBCs) and platelets were altered in patients with chronic periodontitis compared to healthy controls. Study Design:A total of 120 subjects, 60 with chronic periodontitis and 60 with healthy periodontium of age group 30-50 years were selected for the study. Oral hygiene status and pocket probing depth were measured. During clinical evaluation, venous blood samples were taken to analyze the WBC and platelet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
6
19
0
Order By: Relevance
“…In a study with fifty chronic periodontitis patients and fifty control individuals with normal periodontal tissue, Al‐Rasheed () showed that the leukocyte count was higher in the chronic periodontitis patients than in their counterparts (7.22 ± 1.42 × 10 9 cells/L vs 5.64 ± 1.56 × 10 9 cells/L, respectively; P < 0.001). Another case‐controlled study reported that the leukocyte count was higher in patients between 30 and 50 years of age with chronic periodontitis (Kumar et al , ). Furthermore, Pink et al () observed that the leukocyte count was directly correlated with a risk of periodontitis in the German population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with fifty chronic periodontitis patients and fifty control individuals with normal periodontal tissue, Al‐Rasheed () showed that the leukocyte count was higher in the chronic periodontitis patients than in their counterparts (7.22 ± 1.42 × 10 9 cells/L vs 5.64 ± 1.56 × 10 9 cells/L, respectively; P < 0.001). Another case‐controlled study reported that the leukocyte count was higher in patients between 30 and 50 years of age with chronic periodontitis (Kumar et al , ). Furthermore, Pink et al () observed that the leukocyte count was directly correlated with a risk of periodontitis in the German population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection of periodontitis is important from a public health perspective and the leukocyte count could be a useful predictor of this disease. Although previous research has consistently shown a positive association between elevated leukocytes and periodontitis, these were few in number and were small‐sized, randomly sampled population‐based studies (Christan et al , ; Al‐Rasheed, ; Kumar et al , ). And there are few studies to examine the relationship between leukocyte count and periodontitis based on nationwide survey in Asian populations.…”
Section: Introductionmentioning
confidence: 98%
“…Kumar et al [29] found that WBC levels are increased in the case of periodontitis in humans. Rawlinson et al [30] stated that the chronic infl ammatory process may or may not be associated with an increase in the number of WBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in blood flow especially in narrow or blocked arteries due to atherosclerotic plaque formation can be an important etiologic factor for various cardiovascular diseases. 6,7 An increase in number of active thrombocytes can occur in inflammatory and infectious process and this is known as "Reactive Thrombocytosis". 8 Periodontal pathogens such as P. gingivalis and A. actinomycetemcomitans can activate thrombocytes which occurs mainly in the granulation tissue where thrombocytes internalize bacteria or bacterial antigens and as a result produce antimicrobial peptides and cytokines.…”
Section: Introductionmentioning
confidence: 99%